(3cGed GdUfGYJjf GdHjWQI hGdRQObIs - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s ((3eMeO Udi OQhjT edc LQGcSg s)
(3ChdgG (B:s
(3HYO GdMeO ddg , gRe MHT GdXdGe ef YScQ GVjGA , hHYO abO GJe Gddg hLOO SYO ehdGfG TGgQeGf hChai deG QCjJ GdHjGWQI s
(3BNQgG (B:s
(3eSdehf Hjf GdcGa hGdfhf hEfeG GeQg CPG GQGO ddTF Cf jbhd dg cf ajchf adjJhcd GdeDefjf Hejf Ndbf s
(3fSNI KGdKIs
(3hGdMb HGdcJGH CQHY hQbGJ JTJed Ydi ahGFO efbhdI ef cJH GdHjWQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B76s
Keywords: (3GdWHs